How to measure B2B relationship value to increase satisfaction and loyalty. Issue 8 (13th September 2019) - Ruiz-Martínez, Alfonso; Frasquet, Marta; Gil-Saura, Irene
Abstract : Purpose: The purpose of this paper is to analyse the dimensional structure of relationship value by comparing the results of one-dimensional versus multidimensional conceptualisation in the prediction of satisfaction and loyalty in a B2B context. Design/methodology/approach: A survey was carried out and 219 responses were obtained from retail companies in the furniture sector in Spain. The model was estimated using the partial least squares (PLS) approach. Findings: The results revealed that the multidimensional conceptualisation of relationship value explained satisfaction and loyalty levels to a greater extent than the one-dimensional conceptualisation. Research limitations/implications: Given the complexity involved in conceptualising relationship value, its study needs to be expanded to encompass other contexts. Practical implications: Manufacturers should focus their efforts on improving each of the axes of relationship value, to ensure the satisfaction and loyalty of their retail customers. Originality/value: This study integrates and justifies the measurement of relationship value and its axes in the nomological structure with other relational constructs.